RESPON PERTUMBUHAN BIBIT TANAMAN PEPAYA (Carica papaya L.) TERHADAP PEMBERIAN PUPUK ORGANIK CAIR DAUN GAMAL - Mila, Nofri Rihi; Yonce Melyanus Killa, Yonce Melyanus Killa; Lewu, Lusia D. (Jurnal Agroteknologi (Agronu), 2023)
Papaya is a tropical plant that has a fruit that is rich in nutrients such as provitamin A, B vitamins, provitamin C, dietary minerals, lycopene and dietary fiber. The purpose of this study was to determine the growth response of papaya (Carica papaya L.) seedlings to the application of Gamal Leaf Liquid Organic Fertilizer (POC) at different doses. The study was carried out at the Wira Wacana Christian University Sumba agricultural garden laboratory, Kuta Village, Kanatang District, East Sumba Regency from September to October 2022, using a Completely Randomized Design (CRD) with 5 treatments and 4 replicates with P0 as control, P1, i.e. dosing POC is 50 ml/liter of water, P2 is giving a POC dose of 100 ml/liter of water, P3 is giving a POC dose of 150 ml/liter of water, and P4 is giving a POC dose of 200 ml/liter of water. The results showed that the application of leaf POC at various doses did not have a significant effect on the growth of papaya seedlings which included leaf area, stem diameter, number of leaves and plant height. However, the application of gamal leaf POC with a concentration of 200 ml/liter of water gave the highest average value among all treatments. Keyword: Papaya Seed Growth; Liquid Organic Fertilizer; Gamal Leaf